Lexical Cohesion Study in Collection of Hujan Bulan Juni Potery and It’s Relevance as a Literature Learning Material in Junior High School - Muhyidin, Asep (Opción, 2019)
This research focuses on the use of lexical cohesion in collection of poems Hu- jan Bulan Juni. The object of this research is the lexical cohesion includes rep- etition, synonymy, hyponymy, and collocation. This research approach uses qualitative descriptive. The data in this study are linguistic data in the form of lingual units contained in an array and verse containing repetition, synonymy, hyponymy, and collocation in a collection of poems Hujan Bulan Juni. The data collection technique used in this research is direct technique by studying documentation. Analysis of the data in this study was carried out using the dis- tributive method. The findings that there are lexical cohesion which includes: 1) repetition; 2) synonymy, 3) hyponymy and 4) collocation. The most dom- inant lexical cohesion in the poems is repetition. Collection of poems Hujan Bulan Juni can be used as teaching material in junior high school because 1) the language is easy to understand, 2) psychologically according to the level of student development, and 3) in terms of culture reflecting the daily culture of the Indonesian nation.